2022
DOI: 10.1111/1756-185x.14276
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced arthrocentesis of the effusive knee with pneumatic compression

Abstract: Aim: Complete arthrocentesis of the effusive knee ameliorates patient pain, reduces intra-articular and intraosseous pressure, removes inflammatory cytokines, and has been shown to substantially improve the therapeutic outcomes of intra-articular injections. However, conventional arthrocentesis incompletely decompresses the knee, leaving considerable residual synovial fluid in the intra-articular space. The present study determined whether external pneumatic circumferential compression of the effusive knee per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…The same brace was used in another study, which also demonstrated an increase of 72.1% in absolute [27]. Brahmbatt et al used pneumatic compression in a comparative trial and found significant increase in synovial fluid uptake [39] compared to no compression while seated in 90° flexion. As opposed to the other studies, the authors made use of an inexpensive and commonly owned cuff, such as a thigh blood pressure leg cuff.…”
Section: Compression (Table 1 Seventh Column)mentioning
confidence: 92%
See 1 more Smart Citation
“…The same brace was used in another study, which also demonstrated an increase of 72.1% in absolute [27]. Brahmbatt et al used pneumatic compression in a comparative trial and found significant increase in synovial fluid uptake [39] compared to no compression while seated in 90° flexion. As opposed to the other studies, the authors made use of an inexpensive and commonly owned cuff, such as a thigh blood pressure leg cuff.…”
Section: Compression (Table 1 Seventh Column)mentioning
confidence: 92%
“…Arthrocentesis using LMP and MMP were performed with patients in supine positions with either full knee extension or a slight flexion of 0°-20° [20,22,24,30,31,35,38,43], while AL and AN were predominantly performed on patients in seated positions with flexed knees (90°) [20,22,28,30,35,[37][38][39]43].…”
Section: Data Collectionmentioning
confidence: 99%